2016
DOI: 10.1017/ice.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Utilization and Opportunities for Stewardship Among Hospitalized Patients With Influenza Respiratory Tract Infection

Abstract: The majority of patients with influenza RTI received antibiotics on admission, and 34.5% were inappropriately continued on antibiotics without evidence of bacterial infection, which led to increased LOS, loss of net revenue, and no improvement in outcome. Thus, stewardship initiatives aimed at this population are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Treatment duration, however, was relatively short, with a duration longer than five days in only 16% of the patients. Continuation of antibiotics after confirmation of the viral aetiology is not unique to COVID-19 [26,27]. Moreover, randomized controlled studies have not shown a consistent effect of point-of-care testing for influenza on antibiotic prescription rates [28].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment duration, however, was relatively short, with a duration longer than five days in only 16% of the patients. Continuation of antibiotics after confirmation of the viral aetiology is not unique to COVID-19 [26,27]. Moreover, randomized controlled studies have not shown a consistent effect of point-of-care testing for influenza on antibiotic prescription rates [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in North Carolina, discontinuation of antibacterials within 48 h following respiratory viral testing with or without PCT was observed in only 10 to 20% of the cases studied (138). In another study, more than a third of the patients with a positive influenza PCR test result were continued on antibiotics more than 24 h after the availability of the test result, suggesting that additional diagnostic tools-an evaluation of the host response that could indicate the presence of a bacterial, viral, or combined infection-or interventions may be required to convince clinicians that antibiotic discontinuation is safe for these patients (139). If used, ease of availability, rapid turnaround time, and prompt notification of results are essential for promoting appropriate antiviral therapy and timely discontinuation of antibacterials when not otherwise indicated (140).…”
Section: Viral Molecular Assaysmentioning
confidence: 99%
“…In a single-center retrospective review of 166 adults admitted with a respiratory tract infection secondary to influenza, 35% were continued on antimicrobial therapy despite positive influenza test results and negative bacterial cultures. 50 This group had a longer hospital length of stay and higher hospital costs compared with patients in whom antibiotics were stopped. Whether these adverse outcomes represent direct effects of continuing antibiotics or result from appropriate antibiotic use in patients at greater risk of bacterial superinfection is unclear.…”
Section: Does Testing Work?mentioning
confidence: 95%